Kinoids: a family of immunogens for active anticytokine immunotherapy applied to autoimmune diseases and cancer. (May 2010) - Bizzini, Bernard; Drouet, Béatrice; Zagury, Daniel; Abitbol, Marc; Burny, Arsène; Boissier, Marie-Christophe
The complex homeostasis of tissues is coordinated by the cytokine network and imbalances in this network may result in chronic immune disorders. Key specific cytokines, such as TNF-α, IFN-α, IL-4 or VEGF have been demonstrated to be overproduced or abnormally released in the microenvironment of pathologic tissues. These findings have opened up the way to passive immunotherapy with anticytokine monoclonal antibodies. Even though passive immunotherapy has proved to be efficient, it is hampered by specific limitations. The discovery of a family of immunogens, the kinoids, consisting of inactivated cytokine derivatives, has led some to propose them for active immunotherapy as an alternative to passive immunotherapy. This review focuses on kinoids – on their validation in experimental mouse models and ongoing clinical trials. The advantages offered by this active immune therapy in terms of efficacy, safety and patient compliance will be stressed.